PENINGKATAN NILAI TAMBAH DAN PENGOLAHAN PURUN (Lepirona articulata) DI DESA PADANG LUAS KECAMATAN KURAU KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Fitri Mahyudi; Husinsyah; Nisa Ariyanti (Fakultas Pertanian UVAYA Banjarmasin, 2024)
Padang Luas Village, which is located in Kurau District, has long been known as one of the purun producing areas, especially the purun Tikus type in the southern region of Tanah Laut Regency, South Kalimantan Province. It cannot be denied that the focus of purun plant utilization activities is not only related to increasing the productivity (volume) of results, but also increasing the quality of the purun produced. This is a factor that cannot be ignored, because product quality is the main reference for customers in determining the choice of variants spread on the market. This means that quantity and quality are two things that cannot be separated, on the one hand the volume of harvest must be able to maintain the stability of product needs, but on the other hand, product quality must not be neglected just because of pursuing the volume of market demand. Therefore, this service activity is focused on efforts to improve post- harvest quality based on processing purun into goods that can have economic and tourism value. Bearing in mind, until now the Purun farmer group in this area still uses manual methods which makes the process longer and quite tiring and has an impact on product quality. This has been accompanied by a transfer of technology to the Purun Tikus farmer group in the service area. The method used is as follows: (a). Counseling on strategies for improving the quality of purun purun Tikus commodities; (b). Training on transfer of technology for the use of purun plants; and (c) Discussion of the evaluation of the results of the counseling and training that has been carried out as recommendation material for community service activities in the following year